Comparing maximal mean and critical speed and metabolic powers in elite and sub-elite soccer - Lord, C.; Blazevich, A. J.; Abbiss, C. R.; Drinkwater, E. J.; Ma`ayah, F. (International Journal of Sports Medicine, 2020)
The quantification of maximal mean speed (MMS), maximal mean metabolic power (MMPmet), critical speed (CS) and critical metabolic power (CPmet) was conducted over full A-League (elite) and National Premier League (NPL; sub-elite) seasons. Comparisons were made between levels of soccer competition and playing positions (i. e. centre backs, full backs, central midfielders, wide midfielders and strikers). A symmetric moving average algorithm was applied to the GPS raw data using specific time windows (i. e. 1, 5, 10, 60, 300 and 600 s) and maximal values were obtained. Additionally, these maximal values were used to derive estimates of CS and CPmet. Maximal mean values, particularly during smaller time windows (i. e. 1 and 5 s), were greater in A-League match play. Only MMPmet1 was identified as being consistently different between competitions (P=<0.001-0.049) in all playing positions. Significance was only observed in CS (P=0.005) and CPmet (P=0.005) of centre backs between competitions. Centre backs were identified as the least energy demanding playing position. The present findings suggests that both maximal mean and critical analyses are suitable alternatives to common absolute distance and speed assessments of match running performance during competitive matches.